Precarização e deterioração do trabalho no Brasil: características históricas e o cenário atual. - Bertoni Neto, João (2013)
This study aims at analyzing the process of precariousness, deterioration and restructuring of the Brazilian labor market during the decades of 1990 and 2000. However, before addressing the most recent period of the national labor market, has been done a retrospective about the formation and evolution of the Brazilian labor market and its relationship with the precariousness of work. The research proposal is grounded in the use of secondary sources, including: a) bibliographical research to analyze the formation and evolution of the Brazilian labor market and its relationship with the precariousness of the workforce; and b) research in database to give support the discussion on the organization of the Brazilian labor market in the decades of 1990 and 2000. The database utilized has been done the Pesquisa Nacional por Amostra de Domicílios (PNAD). It was observed that the deterioration and precariousness of work are present in Brazil since before the formation of the national labor market, as well as is present nowadays. Therefore, the current characteristics of the Brazilian labor market are related to the formation and evolution of relations and work conditions present in the country, as well as with the new operating conditions of the Brazilian economy introduced in the decade of 1990 subordinated to the interests of foreign capital.